2014
DOI: 10.1017/s0021859614000616
|View full text |Cite
|
Sign up to set email alerts
|

Selection of tomato genotypes resistant to tomato leaf curl virus disease using biochemical and physiological markers

Abstract: SUMMARYA total of 34 tomato genotypes (24 F1+10 parents) were tested for resistance to tomato leaf curl virus (ToLCV) disease by various whitefly inoculation techniques under field and insect-proof glasshouse (mass and cage) conditions. Of the ten tomato parental lines, two accessions [EC-520061 (Solanum habrochaites) and EC-521080 (Solanum pimpinellifolium)] were identified as highly resistant while four accessions (EC-520049, EC-528372, WIR-5032 and WIR-3957) of wild species were resistant to ToLCV. Out of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Bertamini et al, (2002) and Hemida (2005) observed almost similar outcomes with our findings that chlorophyll contents of virus infected leaves were found to be reduced at maximum temperature. Our experimental results are also comparable with Singh et al, (2014) who investigated that occurrence of TLCV has a significant effect on chlorophyll concentration in infected host plant which exhibit very close association among susceptible and resistant genotypes. Chlorophyll concentration reduced in infected virus plants at high temperature has been studied many scientists which might be due to chlorosis which are more frequently occurred in the infected leaves.…”
Section: Discussionsupporting
confidence: 89%
“…Bertamini et al, (2002) and Hemida (2005) observed almost similar outcomes with our findings that chlorophyll contents of virus infected leaves were found to be reduced at maximum temperature. Our experimental results are also comparable with Singh et al, (2014) who investigated that occurrence of TLCV has a significant effect on chlorophyll concentration in infected host plant which exhibit very close association among susceptible and resistant genotypes. Chlorophyll concentration reduced in infected virus plants at high temperature has been studied many scientists which might be due to chlorosis which are more frequently occurred in the infected leaves.…”
Section: Discussionsupporting
confidence: 89%
“…From this, we conclude that the viral infection increased the sugar accumulation and decreased the photosynthetic properties (chlorophyll "a" and "b"). The increase or decrease in VBN (Bg) 6 is not very high and it indicates that the nature of moderate resistance in VBN (Bg) 6 is due to its better photosynthetic properties and less accumulation of sugar, and our findings agree with the statements of Singh et al (2015), Souza et al (2017), andPatwa et al (2020).…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were given for Arka vikas by [13] as a susceptible variety with 76.67 PDI. Based on the coefficient of infection, [14] screened nine tomato genotypes (viz., EC-520049 (S. chmielewskii), EC-520058, EC-520060 and EC-520061 (S. habrochaites), EC-520070, EC-520071, EC-520077, EC-520079 (S. pimpinellifolium) and H-88-78-1(S. lycopersicum; a derivative of S. habrochaites f. glabratum) and were found to be highly resistant. The results are further supported by [15] , who screened thirty five tomato genotypes including wild accessions for its resistance/susceptible reaction against tomato leaf curl disease in field condition during summer cropping season 2015.…”
Section: Screening For Tolcv Resistance Under Field Conditionmentioning
confidence: 99%